2012
DOI: 10.1136/sextrans-2011-050150
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Gram stain in the diagnosis of urethritis in men

Abstract: The low sensitivity of Gram stain means that negative results do not exclude the presence of urethritis in symptomatic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 18 publications
1
11
1
Order By: Relevance
“…In this study we found a relatively high sensitivity of Gram stain analysis for urogenital CT in both periods (83.8% in the 2008–2009 period and 91.0% in the 2010–2011 period) compared with the sensitivity reported by other studies, ranging from 23% to 71% 10 11. The relative high sensitivities in our study could be due to a selective study population that consisted of high- risk patients of which the majority were men who have sex with men (respectively 56.5% and 64.8% of the study populations) compared with more general populations in other studies.…”
Section: Discussioncontrasting
confidence: 52%
“…In this study we found a relatively high sensitivity of Gram stain analysis for urogenital CT in both periods (83.8% in the 2008–2009 period and 91.0% in the 2010–2011 period) compared with the sensitivity reported by other studies, ranging from 23% to 71% 10 11. The relative high sensitivities in our study could be due to a selective study population that consisted of high- risk patients of which the majority were men who have sex with men (respectively 56.5% and 64.8% of the study populations) compared with more general populations in other studies.…”
Section: Discussioncontrasting
confidence: 52%
“…AO stain was more sensitive than the Gram stain in our study. Studies have reported the sensitivity of Gram stain between 40 and 93% [15][16][17][18]. The sensitivity of AO in this study was similar to that reported by Neeraja et al [10].…”
Section: Discussionsupporting
confidence: 90%
“…trachomatis 11%-50% (7, 8, 9, 10, 11, 12-14, 15, 16, 17, 18, 19-25) M. genitalium 6%-50% (7-9, 26, 27, 10, 11, 13, 15, 16, 17, 18, 21, 23-25, 28) Ureaplasmas 11%-26% (8,13,15,17,23,25,29,30) T. vaginalis 1%-20% (8,9,10,31,17,32) Adenoviruses 2%-4% (11, 33) Herpes simplex virus 2%-3% (11,34) . Men with a urethral discharge have a higher bacterial load than those without.…”
Section: Micro-organism Prevalence Referencementioning
confidence: 99%